PENGARUH FINANCIAL DISTRESS DAN STRUKTUR CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN INFORMASI SUKARELA - Randy Yosua Immanuel; Dul Muid (Diponegoro Journal of Accounting, 2015)
This study aims to examine the impact of Financial Distress Status and Corporate Governance structure on the level of voluntary discloure. Financial Distress is proxied by company which recorded negative net income for two consecutive years. Corporate Governance structure is proxied by the board commissioner’s independence, audit committee’s independence, board meeting frequency, audit committee meeting frequency, and audit committee’s competence. The population used in this study is the non-financial companies listed in the Indonesia Stock Exchange over the period of 2010-2013 tallying 140 samples. Sampling technique used in this study is the purposive sampling method and data analysis is done by using the multiple linear regression through the use of SPSS 16 program. Results shown in this study show that Financial Distress has a significant impact on the level of voluntary disclosure. Audit committe’s independence, audit committee meeting freqeuncy and audit committee’s competence have significant positive impact on the level of voluntary disclosure. Whereas board commissioner’s independence and board commissioner meeting frequency do not have significant impact on the level of voluntary disclosure.